The role of electronic payment services in improving the strategic performance of insurance companies : Applied research (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to clarify the nature of the correlation and impact relationship of electronic payment services, represented by its dimensions (marketing, procedures, reliability, cost, and service quality), in improving the strategic performance of Iraqi insurance companies, represented by its dimensions (financial performance, customers, internal processes, sustainability, growth, and learning). The research problem is embodied in the weak performance of the two studied companies due to their lack of electronic payment services, which has weakened their ability to achieve their strategic objectives.The research adopts a descriptive-analytical approach using a questionnaire, which was distributed to a sample of (287) employees from the National Insurance Company and the Iraqi General Insurance Company. Additionally, financial data from the years (2018–2022) was utilized. The research relied on the SPSS statistical program to calculate Pearson’s correlation coefficient and the regression equation. The results showed a strong positive and significant correlation, as well as a positive impact of electronic payment services on improving the strategic performance of insurance companies.